El espacio imaginario y la memoria en tres novelas de Julio Llamazares: Luna de Lobos, La lluvia amarilla y El cielo de Madrid (XXI Century. Spanish Literature and Culture, 2013)
The research aims to investigate the presence and the treatment of the memory and the space in The yellow rain, Wolves moon and the Madrid’s sky. The first part deals with the narrative structure of the three novels. The second part investigates the circulation between the imaginary space and real space. In the third part, we will present the interaction between memory and narrative space as well as their symbolic significance. Basically, the space is a relevant element of the three novels, which not only helps to create possible worlds, making them credible to readers, but also is an indissoluble link with the problematic and complex condition of the human being. In fact, the imaginary space of three novels has an important symbolic significance of solitude, decay and death. By means of the construction of imaginary space, Llamazares is able to recreate the narrative originality.
Keywords: space; imaginary; Llamazares; memory